Tests as the method of students’ knowledge assessment - Berezovska, Olga (My University, 2012)
The article is concerned with the test method, main types of tests and their application for the assessment of students’ knowledge
Keywords: тести; тесты; tests; метод тестування; оцінювання; основні види тестів; метод тестирования; оценка; основные виды тестов; test method; assessment; evaluation; main types of tests; кафедра ділової іноземної мови та міжнародної комунікації